Multimodal cohesion in perfume advertisement - Нікіфорова , Євгенія; Popivniak , Olena; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article deals with the investigation of perfume advertisement in the aspect of its semiotic mode cooperation and interactions which are reflected as cohesion within one and the same semiotic mode and between different semiotic modes as well. The objects of the research are perfume advertisements and their formal elements which create the semiotic structure. Within the verbal semiotic mode, such leading formal elements as functional blocks, subblock names and their lexical embodiment were distinguished. The most developed functional block contains name, naming complex with A-1 brand (company), B-2 individual name, C-3 genitive (product) name, and D-4 additional information. These names are the key markers of lexical cohesion. Lexical cohesion within the verbal semiotic mode is realised through the mechanism of reiteration, including repetition and synonym usage. Lexical cohesion occurs within one and the same functional block as well as between different functional blocks. Within the visual semiotic mode, there are such formal elements as composition, plan, balance, and depth. The advertisement visual semiotic mode has such a set of parameters as a plan, visual component, variable and constant details of a visual component. The advertisement depth is realised using front, middle, and back plans. The main visual components are a perfume bottle, model and scenery. The model has the most detailed visual representation including the model's image, code of costume, and code of behaviour (grasping body language – pose, imitation of behaviour and facial expression). Colour as a media language is closely connected with the process of visualisation and occurs in all visual components providing visual repetition as a basic colour or its shade. Visual components (objects) are repeated in different plans, providing further cohesion between different plans. There is a definite correlation between verbal components-naming units and their visualisation. It is the case of further cohesion between verbal and visual semiotic modes. The olfactory semiotic mode uses the mechanism of synaesthesia when smell is represented involving verbal description and optical visualisation but this aspect of research needs more detailed investigation and deeper revealing and analysis.
Keywords: formal element, lexical cohesion, multimodal cohesion, parameter of mode, perfume advertisement, semiotic mode.